Respuesta :
Answer:
t=1/2
Step-by-step explanation:
4(t+1/4)=3
t+1/4=3/4
t=3/4 - 1/4
t=2/4=1/2
Answer: t = 1/2
Step-by-step explanation: First, we need to get rid of the parentheses on the left side of the equation. We can do this by multiplying the number outside the parentheses by everything inside the parentheses:
4(t+1/4)=3
4t + 4 · 1/4 = 3
4t + 1 = 3
Now, we need to move the 1 to the right side of the equation, so we can isolate the x. If we move a number from one side of the equation to the other, then it will change signs. (- or +)
4t = 3 - 1
4t = 2
Now, let's divide both sides by 4 to isolate x.
4t/4 = 2/4
t = 1/2